Oracle database foundations - Bryla, Bob (Sybex, 2004)
The world of IT is always evolving, but in every area there are stable, core concepts that anyone just setting out needed to know last year, needs to know this year, and will still need to know next year. The purpose of the Foundations series is to identify these concepts and present them in a way that gives you the strongest possible starting point, no matter what your endeavor. Oracle Database Foundations provides essential knowledge about installing, configuring, maintaining, and querying Oracle 9i and 10g databases. What you learn here will benefit you in the short term, as you acquire and practice your skills, and in the long term, as you use them. Topics covered include: Basic relational database concepts Reporting and querying using SQL*Plus and iSQL*Plus Creating and maintaining a database Managing user access and security Understanding Oracle database functions Using multiple tables in a query Restricting, sorting, and grouping data Optimizing database performance Creating backups Troubleshooting database errors.